Unix and C / A Tutorial Introduction - Cornes Philip (Chapman & Hall, 1989)
This book offers a sound tutorial introduction to both UNIX and C, concentrating specifically on the facilities that will be most useful and interesting to the beginner. Acknowledgements, Preface, Introduction, The UNIX Operating System, UNIX Basics, Shell Basics, Editing Files, UNIX Utilities, The C Programming Language, Functions and Arguments, Pointers and Arrays, Structures and Unions, UNIX and C, UNIX System Interface, C in Action, The SHELL in Action, Exercises, Index.